The information gap in corporate annual reports: evidence from Egypt. (1st January 2012) - Hassan, Omaima A.G.; Giorgioni, Gianluigi; Romilly, Peter; Power, David M.
This study explores whether an information gap exists for six types of corporate disclosure in Egypt, where International Accounting Standards (IAS) apply but penalties for non-compliance are limited. It also investigates whether low compliance with mandatory disclosure can be explained by low levels of demand for this type of information among local financial analysts. The results identify a significant gap between actual disclosure practices of companies for various types of disclosure and market perceptions of this practice. Our findings also suggest that low compliance with disclosure requirements in Egypt is not driven by low levels of demand from local financial analysts, because these items of information are perceived as useful for investment decision making.